Market failure in the municipal economy - Piotr Jeżowski (Ekonomia i Prawo, 2009)
The aim of this paper is, firstly, to assess the main factors of market failure in the municipal economy and, secondly, to show its practical consequences for the regulatory framework. The municipal market failure follows from market inefficiency connected mainly with natural monopoly and partially from imperfect information, uncertainty, externalities and instability. The nature of municipal markets is also influenced by a sui generis cost mechanism in network-dependent companies,  high barriers of entry and their general profile of services (i.e. social goods, low demand elasticity). Noncompetitive (monopolistic) markets should and must be regulated and the main field of the municipal companies regulation is ratemaking as a rate of return regulation or price-caps regulation.